2023
DOI: 10.1038/s41467-023-36485-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interplay between non-coding enhancer transcription and gene activity in development

Abstract: Non-coding transcription at the intergenic regulatory regions is a prevalent feature of metazoan genomes, but its biological function remains uncertain. Here, we devise a live-imaging system that permits simultaneous visualization of gene activity along with intergenic non-coding transcription at single-cell resolution in Drosophila. Quantitative image analysis reveals that elongation of RNA polymerase II across the internal core region of enhancers leads to suppression of transcriptional bursting from linked … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…The higher transcript level of the truncated cry1Ac gene than that of the full-length cry1Ac gene may be one of the reasons why the Cry1Ac insecticidal protein content of R7569 was higher than that of MON531. However, genes with higher transcription levels do not necessarily exhibit the same level of protein expression, so the fact that the truncated gene can be transcribed normally and has a high transcription level does not directly infer the excellent performance of its exogenous insecticidal protein content and biological functional activity [18]. It has been shown that different cry1Ac protein contents were correlated with bollworm survival, and that as the cotton growing season lengthens and plant maturity increases, the Cry1Ac insecticidal protein content decreases, accompanied by an increase in bollworm survival [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The higher transcript level of the truncated cry1Ac gene than that of the full-length cry1Ac gene may be one of the reasons why the Cry1Ac insecticidal protein content of R7569 was higher than that of MON531. However, genes with higher transcription levels do not necessarily exhibit the same level of protein expression, so the fact that the truncated gene can be transcribed normally and has a high transcription level does not directly infer the excellent performance of its exogenous insecticidal protein content and biological functional activity [18]. It has been shown that different cry1Ac protein contents were correlated with bollworm survival, and that as the cotton growing season lengthens and plant maturity increases, the Cry1Ac insecticidal protein content decreases, accompanied by an increase in bollworm survival [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one possibility is that the dissolution of the cluster in these examples is caused by DNA supercoiling generated by transcription, which can destabilize DNA-bound factors and block transcription [ 99 , 100 ]. In addition, such a negative feedback loop may arise if these clusters coactivate noncoding transcription at enhancers, which then dislodges DNA-bound TFs and dissolves the cluster [ 101 ]. Apart from gaining a more detailed understanding of the underlying mechanisms, future studies are needed to reveal the extent to which these self-limiting bursts are prevalent across different contexts.…”
Section: Local Genome Architecturementioning
confidence: 99%